Developing Organizational Strategy - Marpaung, Hendru; Isa Indrawan, Muhammad (PT. Multidisciplinary Press Indonesia, 2024)
The first step in managing human resources is to assign human resources so that they obtain work assignments that are appropriate for the work being done. Human resources (HC) or staff members have become a top priority in any organization as their quality is crucial in facing the current business climate. This research aims to examine the influence of leadership style, human resource quality and organizational citizenship behavior (OCB) on organizational commitment in communication mediation at the Bank Indonesia Representative Office, North Sumatra Province. The results of this research are as follows: Leadership Style has a positive and significant effect on Organizational Commitment with an original sample value of 0.374 and ap value of 0.001. Leadership style has a positive and significant effect on communication with an original sample value of 0.368 and ap value of 0.001. Communication has a positive and insignificant effect on Organizational Commitment with an original sample value of 0.100 and ap value of 0.179. HR quality has a positive and significant effect on Organizational Commitment with an original sample value of 0.289 and ap value of 0.005. HR quality has a positive and insignificant effect on communication with an original sample value of 0.205 and ap value of 0.070. Organizational Citizenship Behavior has a positive and insignificant effect on Organizational Commitment with an original sample value of 0.178 and ap value of 0.053. Organizational Citizenship Behavior has a positive and significant effect on Communication with an original sample value of 0.332 and ap value of 0.004. Leadership style has a positive and insignificant effect on Organizational Commitment through communication with the original sample of 0.037 and p value 0.171. HR quality has a positive and insignificant effect on Organizational Commitment through Communication with an original sample value of 0.020 and ap value of 0.290. Organizational Citizenship Behavior has a positive and significant effect on Organizational Commitment through Communication with an original sample value of 0.020 and an ap value of 0.212.